Implementation of a rainwater harvesting network to manage stormwater runoff in Manhattan, Kansas - Musoke, Elizabeth (Kansas State University, 2012)
The City of Manhattan, Kansas has been subject to intense flooding in the last couple of years. Areas of the city, within the Wildcat Creek Watershed, have been adversely affected. The City of Manhattan and stakeholders from various walks of life are looking for solutions to alleviate flooding within the area. This Master’s Project looks into rainwater harvesting as one of the solutions to help reduce stormwater runoff and contribute to the alleviation of flooding within the Watershed. Rainwater harvesting is increasingly being recognized as an effective way to reduce stormwater runoff. The project explores the potential benefit of using a network of rainwater harvesting elements, namely rain barrels and cisterns supplemented by rain gardens and other infiltration methods to reduce runoff in the City of Manhattan, Kansas. To assess the benefit of using rainwater harvesting in the City, a neighborhood scale site was chosen and divided into land use types. Three phases were used to assess the impact and implementation of rainwater harvesting. Phase I calculates the volume of runoff generated from each land use type and how much of that runoff can be harvested from the rooftops. The values from the neighborhood scale analysis were then extrapolated to see the impact of rainwater harvesting on a larger scale. Phase II looks at the configuration of a rainwater harvesting system for the structures in each land use type and rainwater reuse options. Finally, Phase III looks at policies, regulations and incentives that can be employed by the City of Manhattan to help encourage rainwater harvesting. This Master’s project seeks to educate the City and its residents about the benefits of rainwater harvesting as a stormwater management tool and provide steps towards potentially using rainwater harvesting as a way to reduce runoff, and help alleviate flooding in the Wildcat Creek Watershed.
Keywords: Rainwater harvesting; Stormwater management; Policy; Urban planning; Flooding; Sustainability (0640); Urban Planning (0999)